Rewrittings of detective genre in serial fiction: death, the compass and the monster in "Breaking Bad" - Núñez Sabarís, Xaquín (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The series Breaking Bad, original idea of Vince Gilligan, represents cultural (and academic) boom and legitimacy of TV fiction in recent years. The new series offering, covered by a new model of TV and digital business, has led to a renewal of cultural habits, transcending to its consideration of minor audiovisual genres and stimulating an important aesthetic democratization. By incorporating creative talent in the scripts and interpretation, as well as outstanding production, the series has been placed in the zone of audiovisual culture and contemporary artistic narrative, incorporating mechanisms of other media medium, such as literature.The story of Walter White, father of a family and ruthless narco, is built on a plot of intrigue and persecution, which is resolved by a handwritten note on a copy of Leaves of grass. From Whitman to Borges, we will review the cultural and intermedial loans in the creation of this game of mirrors, faltering identities and labyrinthine plots.
Keywords: Borges; Breaking Bad; intermedial narratives; literature; TV series